Exploring doctors’ perspectives on precision medicine and AI in colorectal cancer: opportunities and challenges for the doctor-patient relationship - Mirko Ancillotti; Åsa Grauman; Jorien Veldwijk; Åsmund Flobak; Deborah Mascalzoni (BMC Medical Informatics and Decision Making)
Abstract Background Precision medicine and artificial intelligence (AI) are increasingly integrated into colorectal cancer (CRC) care, offering personalised treatment strategies and data-driven decision support. While these technologies promise improved outcomes, they also raise challenges concerning clinical decision-making, the doctor-patient relationship, and ethics. This study explores physicians’ perspectives on integrating precision medicine and AI in CRC care. Methods A qualitative study was conducted using semi-structured interviews with ten CRC physicians from six European countries. Participants were recruited through purposive and snowball sampling. Interviews were analysed using thematic analysis. Results Three key themes emerged from the analysis. First, physicians described precision medicine as a logical extension of existing tailoring practices, offering new opportunities while introducing complexity. Many expressed concerns about the blurred boundary between experimental and standard treatments, noting potential implications for equity and ethical decision-making. Second, AI was viewed as a future partner in care, with the potential to enhance efficiency and assist in synthesising complex data. However, participants voiced concerns about trust, clinical responsibility, and the lack of regulatory clarity, particularly due to AI’s “black box” nature. Finally, doctors reported challenges in communicating both precision medicine and AI-based recommendations to patients. They emphasised the importance of adapting communication strategies to individual patients and highlighted the need for structured approaches to ensure patient understanding and prevent miscommunication, especially when dealing with uncertain outcomes or emerging technologies. Conclusions The findings highlight both the opportunities and challenges of integrating precision medicine and AI in CRC care. Addressing concerns related to communication, ethics, and regulation requires clear guidance and improved support for clinicians. Precision medicine and AI enhance CRC care but demand robust communication, regulation, and ethical safeguards to ensure transparency, trust, and physician autonomy.